2014
DOI: 10.1097/ccm.0b013e3182a27909
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Nitric Oxide Does Not Reduce Mortality in Patients With Acute Respiratory Distress Syndrome Regardless of Severity

Abstract: Nitric oxide does not reduce mortality in adults or children with acute respiratory distress syndrome, regardless of the degree of hypoxemia. Given the lack of related ongoing or recently completed randomized trials, new data addressing the effectiveness of nitric oxide in patients with acute respiratory distress syndrome and severe hypoxemia will not be available for the foreseeable future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
133
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(143 citation statements)
references
References 57 publications
3
133
0
7
Order By: Relevance
“…On arrival back at our centre, the median (IQR [range]) Acute Physiology And Chronic Health Evaluation (APACHE) II and maximum Sequential Organ Failure Assessment (SOFA) scores were 17 (14-21 ) and 12 (9-15 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]), respectively. After transfer on ECMO, there were significant improvements in PaO 2 /F I O 2 ratio, ventilator F I O 2 , plateau mechanical ventilation pressure, pH and arterial PCO 2 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On arrival back at our centre, the median (IQR [range]) Acute Physiology And Chronic Health Evaluation (APACHE) II and maximum Sequential Organ Failure Assessment (SOFA) scores were 17 (14-21 ) and 12 (9-15 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]), respectively. After transfer on ECMO, there were significant improvements in PaO 2 /F I O 2 ratio, ventilator F I O 2 , plateau mechanical ventilation pressure, pH and arterial PCO 2 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The use of lungprotective ventilation, early neuromuscular blockade, mechanical ventilation of the lungs in the prone position, conservative fluid strategies and low-dose corticosteroids have all been shown to improve outcomes in patients with ARDS [2][3][4][5][6][7]. Beyond these therapies, the use of extracorporeal membrane oxygenation (ECMO) has shown promising results in patients with severe respiratory failure [8][9][10][11][12][13], while other rescue therapies such as high-frequency oscillatory mechanical ventilation and inhaled nitric oxide have shown no demonstrable mortality benefit [14][15][16][17]. In England, five severe respiratory failure centres have been commissioned to deliver complex respiratory support, including ECMO.…”
Section: Introductionmentioning
confidence: 99%
“…5 Inhaled NO and aerosolized prostacyclin improves ventilation/perfusion matching by increasing circulation to better-ventilated alveoli and reducing pulmonary hypertension associated with ARDS. Adhikari et al 6 examined the effect of inhaled nitric oxide on in-hospital mortality in subjects with severe ARDS (P aO 2 /F IO 2 Յ 100 mm Hg). The meta-analysis included data from 9 trials with 1,142 subjects.…”
Section: See the Original Study On Page 127mentioning
confidence: 99%
“…The meta-analysis included data from 9 trials with 1,142 subjects. 6 They concluded that inhaled NO does not reduce mortality. Another meta-analysis of 25 studies showed that inhaled prostacyclin improved oxygenation and decreased pulmonary artery pressures but may be associated with harm by producing hypotension.…”
Section: See the Original Study On Page 127mentioning
confidence: 99%
“…The underlying rationale of using inhaled pulmonary vasodilators is based on the pathology of ARDS involving mismatching of ventilation and perfusion and pulmonary hypertension. However, in 2007 Adhikari et al conducted a meta-analysis of 12 trials with a total of 1,237 patients showing that inhaled NO (iNO) is associated with limited improvement in oxygenation in patients with severe ARDS and has no beneficial effect on mortality (19). It may even cause harm by promoting renal dysfunction.…”
mentioning
confidence: 99%